2017
DOI: 10.1177/2156587217715927
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Yoga as a Form of Treatment for Depression

Abstract: The purpose of this article was to systematically review yoga interventions aimed at improving depressive symptoms. A total of 23 interventions published between 2011 and May 2016 were evaluated in this review. Three study designs were used: randomized control trials, quasi-experimental, and pretest/posttest, with majority being randomized control trials. Most of the studies were in the United States. Various yoga schools were used, with the most common being Hatha yoga. The number of participants participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…Furthermore, social detachment was demonstrated as an important religious coping practice for managing death anxiety (Maheshwari and Mukherjee 2019). Spiritual practices such as a daily schedule of yoga and meditation were found to be effective in relieving symptoms of depression and anxiety (Bridges and Sharma 2017;Varambally and Gangadhar 2020), which may provide great relief from death anxiety as well.…”
Section: Religious Coping With Death Anxietymentioning
confidence: 99%
“…Furthermore, social detachment was demonstrated as an important religious coping practice for managing death anxiety (Maheshwari and Mukherjee 2019). Spiritual practices such as a daily schedule of yoga and meditation were found to be effective in relieving symptoms of depression and anxiety (Bridges and Sharma 2017;Varambally and Gangadhar 2020), which may provide great relief from death anxiety as well.…”
Section: Religious Coping With Death Anxietymentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) and open studies have found yoga to be beneficial in treating unipolar depression. 19 22 On its own or as an adjunct to medication, yoga has been shown to alleviate symptoms of mild to moderate depression. 23 Preliminary evidence suggests that it may even benefit more severe depression and even alleviate suicidal ideation.…”
Section: Yoga For Depressionmentioning
confidence: 99%
“…Complementary therapies such as acupuncture and yoga have a developed evidence base for other health conditions (Bridges & Sharma, 2017 ; Smith, Armour, Lee, Wang, & Hay, 2018 ) but it is perhaps surprising that these are recommended above other established alternative approaches such as meditation. This may, however, reflect the dearth of RCTs in this area.…”
Section: Discussionmentioning
confidence: 99%